2009
DOI: 10.1371/journal.pone.0006908
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Plasticity of Striatal Neurons Intrinsic Excitability following Dopamine Depletion

Abstract: The striatum is the major input structure of basal ganglia and is involved in adaptive control of behaviour through the selection of relevant informations. Dopaminergic neurons that innervate striatum die in Parkinson disease, leading to inefficient adaptive behaviour. Neuronal activity of striatal medium spiny neurons (MSN) is modulated by dopamine receptors. Although dopamine signalling had received substantial attention, consequences of dopamine depletion on MSN intrinsic excitability remain unclear. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
9
58
0
2
Order By: Relevance
“…Specifically, dopamine deficiency has been associated with a loss in spines in medium sized spiny neurons [4, 20, 21, 33, 46], and dopamine is being increasingly considered as a potential neuroprotective agent in HD [16, 29, 49]. Therefore, to determine whether alterations in DA transmissions could contribute to the morphological impairments we have observed in older mice, we performed an immunocytochemical stain for TH, a marker of nigrostriatal dopaminergic terminals in the striatum.…”
Section: 0 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, dopamine deficiency has been associated with a loss in spines in medium sized spiny neurons [4, 20, 21, 33, 46], and dopamine is being increasingly considered as a potential neuroprotective agent in HD [16, 29, 49]. Therefore, to determine whether alterations in DA transmissions could contribute to the morphological impairments we have observed in older mice, we performed an immunocytochemical stain for TH, a marker of nigrostriatal dopaminergic terminals in the striatum.…”
Section: 0 Resultsmentioning
confidence: 99%
“…In the present study, we have measured immunoreactivity of TH, the rate-limiting enzyme of catecholamine synthesis and a marker for dopamine terminals in the striatum (which contains very few noradrenergic terminals). Interestingly, several studies have reported an association between striatal dopamine deficiency and spine loss in medium sized spiny neurons [4, 20, 21, 33, 46]. In fact, changes in dopamine function influencing striatal spines in HD could either be pre- or post-synaptic.…”
Section: 0 Discussionmentioning
confidence: 99%
“…All increase in the E max for Ca 2ϩ current modulation by quinelorane after DA depletion (Prieto et al 2009) is virtually due to enhanced D 3 R-type modulation. Supersensitivity contributed by other receptor types belonging to the D 2 R class deserves its own study to relate their signaling with some excitability parameter (Azdad et al 2009). 4) Downregulation of D 3 nf variant in striatum accompanied the enhanced D 3 R-type activity.…”
Section: Discussionmentioning
confidence: 99%
“…As striatal dopaminergic terminals are lost, a variety of compensatory adjustments take place, such as increased DA release from remaining terminals (Snyder et al, 1990; Zigmond et al, 1990; Calne & Zigmond, 1991), decreased reuptake of released DA (Sossi et al, 2007), increased DA synthesis via TH (Loeffler et al, 1995; Bezard et al, 2000), upregulation of post-synaptic DA receptors (Perlmutter et al, 1987; Kaasinen et al, 2000), and increased excitability of the target striatal medium spiny neurons (Azdad et al, 2009). These adaptive changes, which exemplify compensatory activation of alternative effectors in homeostatic negative feedback loops (Goldstein, 2013), maintain dopaminergic functions until the loss of the terminals is advanced.…”
Section: Therapeutic Implications Of Catecholamine Autotoxicitymentioning
confidence: 99%